2006
DOI: 10.1371/journal.pmed.0030477
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Causes of Blindness and Low Vision in Southern Sudan

Abstract: BackgroundBlindness and low vision are thought to be common in southern Sudan. However, the magnitude and geographical distribution are largely unknown. We aimed to estimate the prevalence of blindness and low vision, identify the main causes of blindness and low vision, and estimate targets for blindness prevention programs in Mankien payam (district), southern Sudan.Methods and FindingsA cross-sectional survey of the population aged 5 y and above was conducted in May 2005 using a two-stage cluster random sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
35
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 17 publications
7
35
5
Order By: Relevance
“…However, reports from western countries indicate that AMD and glaucoma are the main causes of blindness in these countries. 5,6 In the Middle East, there are valuable reports from Pakistan, [7][8][9] Sudan, 10 Turkey, 11 and Iran. 12 Although many studies have been performed on ocular diseases in the Middle East in the recent years, they are not comparable in quantity with studies performed in East Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, reports from western countries indicate that AMD and glaucoma are the main causes of blindness in these countries. 5,6 In the Middle East, there are valuable reports from Pakistan, [7][8][9] Sudan, 10 Turkey, 11 and Iran. 12 Although many studies have been performed on ocular diseases in the Middle East in the recent years, they are not comparable in quantity with studies performed in East Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…Six of the 38 children had low vision due to more than three causes while 5 children had at least two causes. Table 1: Causes of low vision by age group vision in our study participant was higher than that reported from other Sub-Saharan Africa countries (Ezepue, 1997;Abu, 2002;Ngondi et al, 2006). Binocular low vision was common among the schoolchildren.…”
Section: Resultsmentioning
confidence: 48%
“…We thank the authors [1,2] for the two perspectives on our articles [3,4]. Our study estimated the prevalence of blindness in Mankien at 4%, which Kuper and Gilbert describe as being “beyond the range” of the studies reviewed by Pascolini et al [5].…”
mentioning
confidence: 95%